A Novel Framework for Nanoscale Wireless Communications Using Minimum Energy Channel Codes (International Journal of Engineering and Computer Science, 2014)
In the world of nanoscale wireless communications, usage of energy plays a vital role in the communications. In our proposed algorithm, a novel minimum energy coding scheme (MEC) and a novel modulation scheme is proposed for wireless nano sensor networks (WSNS). Unlike conventional algorithms, MEC maintains the reliability in the process of minimizing the energy. It is analytically shown that, with MEC, code words can be decoded perfectly for large code distances, if the source set cardinality is less than the inverse of the symbol error probability. The state of-the-art nanoscale power and energy limits are used to obtain high end achievable rates of nano nodes and high performance, which are expected to be on the order of Mbps, neglecting the processing power. Our proposed evaluation results outperform the popular Hamming, golay and Reed-Solomon in the average codeword energy sense.